208 Blunt Splenic Trauma, Retrospective Study 2008–2013, the Canberra Hospital. (28th February 2022) - Khan Hotak, M.; Fitzgerald, A.
Abstract: Aim: To evaluate the management of Blunt Splenic Trauma (BST) management in multi-injured trauma patients at The Canberra Hospital (TCH). Non operative management (NOM) for hemodynamically stable patients & operative management (OM) for unstable patients. The aim was how to further reduce failed NOM. Method: Retrospective data collected from of all multi trauma patients with BST from June 2008 - June 2013 at TCH. Data review included patients' admission notes, CT results, management technique, and clinical outcome. Results: A total of 161 patients included in the study. All paediatric patients treated with NOM with success rate of 100%. Seventy-three per cent of adults managed NOM with success rate of 97.8%. Twenty-six per cent managed operatively. ICU admissions were 54.4 % and splenic angioembolisation 2.9%. Mortality was 3.7 % with multiple injury patients zero with isolated splenic injury Conclusions: As per our study NOM is the standard of care for all hemodynamically stable patients with success rate of 97.8% acceptable rate as per evidence more than 96%. All hemodynamically unstable patients with diffuse peritonitis require urgent laparotomy. The query to answer that AE should be considered for all patients with (AAST) grade 4–5 who are hemodynamically stable as adjunct to NOM to reduce rate of fail NOM. Further randomised controlled studies are needed.